Dari Teologi Normatif ke Emansipasi Sosial: Rekonstruksi Paradigma Tauhidik untuk Masyarakat Tanpa Penindasan - Muhammad Maulidar Rohman; Difa Karimatul Maulidia Azzahra; Mufida Hilmi; Ali Hasan Siswanto (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This article begins with the paradox between the ideals of Islamic theology, which are oriented towards the values ​​of rahmatan lil 'alamin (blessing for the universe) and social realities that are still rife with various forms of structural, cultural, and symbolic oppression. Academic anxiety arises when theology tends to stop at the normative-doctrinal level and has not yet functioned as a force for social transformation. The research gap lies in the absence of integration between theology, social philosophy, and spirituality (Sufism) in formulating an operational and contextual model of a society without oppression. This article uses an integrative theoretical approach based on the tauhidic paradigm that combines the dimensions of revelation, reason, and social reality. The research method used is qualitative through literature study with critical analysis, hermeneutics, and an interdisciplinary approach. The article's main argument asserts that tauhid is not only a theological doctrine but also an emancipatory principle that rejects all forms of domination other than God, thus having direct implications for social liberation. Through this reconstruction, the article offers the concepts of "emancipatory-transformative theology" and "social-progressive Sufism" as a methodological basis for creating a society without oppression. The scholarly contribution of this research lies in the development of a new paradigm in Islamic Studies that integrates theology, philosophy, and spirituality into a framework of social transformation, while also providing a conceptual model applicable to contemporary socio-religious movements.